Morphological Signs of Exposure to Insecticides and Pesticides Mixtures in an Experiment - Nishanov, Yusubjon Nishanovich; Askarovna, Hamrakulova Mukaddaskhon; Usmanovich, Sadikov Askar; Turginbaevich, Mamasaidov Jamolidin (International Journal of Psychosocial Rehabilitation, 2020)
This work is devoted to the question of the effect of pesticides, insecticides and pesticides on the microstructures of internal organs in the experiment. Under experimental conditions, the morphological picture was studied after the use of pesticides and pesticides. The results of morphological studies at different times after seeding with pesticides and pesticides were analyzed. The state of the histostructure of the internal organs was studied.